A Leaderless Two-Peptide Bacteriocin, Enterocin DD14, Is Involved in Its Own Self-Immunity: Evidence and Insights - Ladjouzi, Rabia; Lucau-Danila, Anca; Benachour, Abdellah; Drider, Djamel (Frontiers in Bioengineering and Biotechnology, 2020)
Enterocin DD14 (EntDD14) is a two-peptide leaderless bacteriocin produced by Enterococcus faecalis 14, a strain previously isolated from meconium. EntDD14 has a strong antibacterial activity against Gram-positive bacteria. Leaderless bacteriocins, unlike bacteriocins with leader peptides, are immediately active after their translation, and a producing strain has then to develop specific mechanisms to protect both intra and extracellular compartments. The in silico analysis of Ent. faecalis 14 genome allowed to locate downstream of structural ddAB genes, 8 other adjacent genes, designed ddCDEFGHIJ, which collectively may form three operons. To gain insights on immunity mechanisms of Ent. faecalis 14, mutant strains knocked out in ddAB genes encoding bacteriocin precursor peptides (Δbac) and/or ABC transporter (ΔddI) of EntDD14 were constructed and characterized. Importantly, Δbac mutant strains, from which structural ddAB genes were deleted, resulted unable to produce EntDD14 and sensitive to exogenous EntDD14 showing their involvement in the Ent. faecalis 14 immunity system. Moreover, the sensitivity of Δbac mutants appeared not to be associated with the down-regulation of ddCDEFGHIJ gene expression since they were similarly expressed in both Δbac and wild-type strains during the log phase while they were found significantly down-regulated in the Δbac mutant strain after 24 h of growth. Data gathered from this study suggest also the implication of the ABC transporter (ddHIJ) in the active export of EntDD14 but ruled-out its involvement in the primary self-immunity system. Interestingly, non-bacteriocin producing Ent. faecalis JH2-2 cells transformed with ddAB, or ddAB plus genes encoding the ABC transporter (ddAB-HIJ) did not produce EntDD14 and remained sensitive to its action. Of note, trans-complementation of the Δbac mutant strain with these constructions allowed to recover the WT phenotype. To the best of our knowledge, this is the first study delineating the role of the intracellular two-peptide leaderless bacteriocins in their self-immunity.